Association Between Vasopressin Rebranding and Utilization in Patients With Septic Shock*. Issue 4 (4th October 2021) - Sacha, Gretchen L.; Kiser, Tyree H.; Wright, Garth C.; Vandivier, R. William; Moss, Marc; Burnham, Ellen L.; Ho, P. Michael; Reynolds, Paul M.; Bauer, Seth R.
Abstract : OBJECTIVES: Vasopressin is suggested as an adjunct to norepinephrine in patients with septic shock. However, after vasopressin was rebranded in November 2014, its cost exponentially increased. Utilization patterns of vasopressin after its rebranding are unclear. The objective of this study was to determine if there is an association between the rebranding of vasopressin in November 2014 and its utilization in vasopressor-dependent patients with severe sepsis or septic shock. DESIGN: Retrospective, multicenter, database study between January 2010 and March 2017. SETTING: Premier Healthcare Database hospitals. PATIENTS: Adult patients admitted to an ICU with severe sepsis or septic shock, who received at least one vasoactive agent for two or more calendar days were included. INTERVENTIONS: The proportion of patients who received vasopressin and vasopressin cost was assessed before and after rebranding, and evaluated with segmented regression. MEASUREMENTS AND MAIN RESULTS: Among 294, 733 patients (mean age, 66 ± 15 yr), 27.8% received vasopressin, and ICU mortality was 26.5%. The proportion of patients receiving vasopressin was higher after rebranding (31.2% postrebranding vs 25.8% prerebranding). Before vasopressin rebranding, the quarterly proportion of patients who received vasopressin had an increasing slope (prerebranding slope 0.41% [95% CI, 0.35–0.46%]), with no difference in slope detected after vasopressin rebranding (postrebranding slope, 0.47% [95% CI, 0.29–0.64%]). After vasopressin rebranding, mean vasopressin cost per patient was higher ($527 ± 1, 130 vs $77 ± 160), and the quarterly slope of vasopressin cost was higher (change in slope $77.18 [95% CI, $75.73–78.61]). Total vasopressin billed cost postrebranding continually increased by ~$294, 276 per quarter from less than $500, 000 in Q4 2014 to over $3, 000, 000 in Q1 2017. CONCLUSIONS: After vasopressin rebranding, utilization continued to increase quarterly despite a significant increase in vasopressin cost. Vasopressin appeared to have price inelastic demand in septic shock.